An Analytical Study of Development of Financial Inclusion Indicators in Some Countries of the Maghreb and the Arab Gulf during the Period (2004-2020) - Benaini, Rahima; Chahada, Shady Ibrahim Hasan (Finance and Business Economies Review, 2022)
This study aims to analyse the development of indicators of financial inclusion in a group of Gulf and Maghreb countries during the period from 2004-2020, as the goal behind this analysis is to investigate the reality of financial inclusion in the economies of Arab countries and also to highlight the most important challenges hindering the promotion of financial inclusion at the level of these Arab countries.. Besides, the study concluded that the rates of financial inclusion recorded within the partial indicators in the Arab Gulf countries are relatively high and acceptable to the same extent, and some of the rates recorded even in some developed countries are commercial, this is in contrast to the rates recorded in the Arab Maghreb countries, including Algeria.